Moving on from responsible gambling: a new discourse is needed to prevent and minimise harm from gambling. (July 2020) - Livingstone, C.; Rintoul, A.
Abstract: Objectives: To address the current status of responsible gambling (RG) as the dominant discourse for reducing gambling harm. Study design: The article is a narrative review of relevant literature analysed discursively. Methods: We identified significant texts describing the discourse of RG and analysed these to extract major characteristics and themes of the discourse. These were then subjected to a critique, using the public health discourses as an alternative system for addressing gambling harm. Results: The discourse of RG is inadequate for preventing or minimising gambling harm. A public health–focused approach to prevent and minimise gambling harm is likely to be far more effective but will be opposed by vested interests. Conclusions: It is timely to consider abandoning the discourse of RG. This discourse has been discredited because of its complicity with vested interests and a lack of evidence to demonstrate its efficacy in preventing or reducing harm. A public health response to the prevention of gambling harm is feasible and practical and can and should be further developed and implemented rapidly. Highlights: Responsible gambling (RG) is the established discourse for gambling harm minimisation. However, it is increasingly clear that it is not 'fit for purpose'. RG is an industry-friendly discourse, downloading responsibility for gambling harm to consumers, and ignoring the harm production capacity of gambling products, and the conditions under which they are provided. Gambling products are not immutable and can be modified to reduce the likelihood of harm. Lessons from other areas of public health practice demonstrate that effective harm prevention and minimisation are possible but to do so requires the abandonment of RG and adoption of a public health discourse, focussing on upstream interventions, and significant policy change. Effective harm prevention and minimisation will likely lead to reduction in gambling revenues. However, the health and well-being of the population will likely be enhanced significantly by adoption of such an approach.